Oxford Basic American Dictionary for Learners of English (New York Oxford University Press, 2011)
A dictionary with CD-ROM that supports learners making the transition from picture to text dictionary. It explains content area and academic vocabulary in simple English, marks the 2000 most important words to know, and gives extra help with grammar, spelling, and pronunciation.
Include Colour Illustrations and Index
Keywords: Americanisms -- English language -- United States